Physical properties of lyocell solution-dope phases fibers spun from different solution-dope phases - Kim, DB; Lee, WS; Jo, SM; Lee, YM; Kim, BC (JOHN WILEY & SONS INC, 2002)
The hydration number (n) of NMMO hydrates has a significant effect on the rheological properties and phase of the cellulose solutions in the hydrates. The physical properties of the lyocell fibers spun from the cellulose solutions in NMMO hydrates with different values of n were investigated relative to the phase of the solution dope. NMMO hydrate with n = 1.1 could not fully dissolve cellulose, resulting in a heterogeneous solution. NMMO hydrate with n = 0.72 produced a mesophase solution that exhibited a good spinnability. When NMMO hydrates with n = 0.72 and 1.0 were used, the lyocell fiber spun from 15 wt % solution dope gave higher tensile strength than that spun from 12 wt % solution dope. NMMO hydrate with n = 1.0 produced a lyocell fiber whose tensile strength was slightly affected by spin-draw ratio but the tensile strength of the lyocell fiber prepared from NMMO hydrate with n = 0.72 was monotonically increased with increasing spin-draw ratio. Further, the latter gave higher birefringence. The lyocell fiber spun from 15 wt % solution in NMMO hydrate with n = 0.72 produced finely fibrillated structures. When treated with sonic wave the lyocell fiber prepared from 15 wt % cellulose (DPw 940) solution in NMMO hydrate with n = 0.72 yielded the most serious fibrillation on the fiber surface. (C) 2002 John Wiley & Sons, Inc.
Keywords: N-OXIDE; CELLULOSE; BEHAVIOR; MIXTURES; SYSTEM; WATER